2022
DOI: 10.3390/antibiotics11020260
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in Virulence and Extended Spectrum Beta-Lactamase Gene Profiles among Cefotaxime-Resistant Escherichia coli Wastewater and Clinical Isolates

Abstract: The World Health Organization has identified antibiotic resistance as one of the largest threats to human health and food security. In this study, we compared antibiotic resistance patterns between ESBL-producing Escherichia coli from human clinical diseases and cefotaxime-resistant environmental strains, as well as their potential to be pathogenic. Antibiotic susceptibility was tested amongst clinical isolates (n = 11), hospital wastewater (n = 22), and urban wastewater (n = 36, both influent and treated effl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 94 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…There are significantly fewer studies detecting bla OXA in the African region and they cover Algeria, where bla OXA-1 was detected [ 74 ]; Durban, South Africa, where cefotaxime-resistant E. coli were studied and bla OXA-1 was found as well [ 91 ]; Eastern Cape Province, South Africa, where bla OXA-1-like and bla OXA-48-like variants harbored by Enterobacterales isolated from effluents of WWTPs were noted [ 72 ]; and Tunisia, where C. freundii isolate carrying bla OXA-204 [ 121 ] and Enterobacterales strains possessing bla OXA-1 [ 127 ] were detected. American studies concerning WWTPs also confirm bla OXA presence in bacteria isolated from WWTP samples [ 80 , 90 , 102 , 104 , 119 , 125 , 133 ].…”
Section: Clinically Significant β-Lactam Resistance Genes In Wastewat...mentioning
confidence: 81%
See 3 more Smart Citations
“…There are significantly fewer studies detecting bla OXA in the African region and they cover Algeria, where bla OXA-1 was detected [ 74 ]; Durban, South Africa, where cefotaxime-resistant E. coli were studied and bla OXA-1 was found as well [ 91 ]; Eastern Cape Province, South Africa, where bla OXA-1-like and bla OXA-48-like variants harbored by Enterobacterales isolated from effluents of WWTPs were noted [ 72 ]; and Tunisia, where C. freundii isolate carrying bla OXA-204 [ 121 ] and Enterobacterales strains possessing bla OXA-1 [ 127 ] were detected. American studies concerning WWTPs also confirm bla OXA presence in bacteria isolated from WWTP samples [ 80 , 90 , 102 , 104 , 119 , 125 , 133 ].…”
Section: Clinically Significant β-Lactam Resistance Genes In Wastewat...mentioning
confidence: 81%
“…Liedhegner et al compared E. coli isolated from samples of various environmental compartments from one geographic area (clinical samples, hospital wastewater, and WWTP). The data including antibiotic resistance, virulence, and ESBL gene profiles confirmed high phenotypic and genotypic similarity across strains of these different origins and demonstrated potential health risks related to ESBL transmission [ 125 ]. An interesting study conducted by Raven et al showed genetic relatedness between E. coli isolated from 20 WWTPs in the UK, livestock farms, retail meat, and isolates responsible for human blood infections.…”
Section: Clinically Significant β-Lactam Resistance Genes In Wastewat...mentioning
confidence: 89%
See 2 more Smart Citations
“…(2019) [ 60 ] reported considerable variations in bla OXA concentrations in municipal wastewater. Amador et al (2015) [ 61 ] detected bla OXA in 27.8% of ESBL-E, and Liedhegner et al (2022) [ 62 ], in 86% of cefotaxime-resistant E. coli isolated from HWW. In the present study, bla OXA was the only gene whose abundance differed significantly between HWW samples collected from different sites.…”
Section: Discussionmentioning
confidence: 99%